A family study of vesicoureteric reflux. Issue 2 (April 1978) - Vargas, Aida De; Evans, Kathleen; Ransley, P.; Rosenberg, A. R.; Rothwell, D.; Sherwood, T.; Williams, D. I.; Barratt, T. M.; Carter, C. O.
Abstract : Vesicoureteric reflux is now considered to be due essentially to congenital malformation of the vesicoureteric junction. It is also considered to be a major cause of renal failure in early adult life. The condition is associated with recurrent urinary tract infection and in some instances with renal scarring. When reflux is detected clinically, in the investigation of patients with recurrent urinary tract infection, renal scarring is often already present. The reflux tends to disappear in later childhood. A family study has been made based on 186 index patients with established primary reflux, with special attention to a history of genitourinary symptoms in the sibs and parents of these patients. There were 39 sibs under the age of 4 years. For these the parents were offered investigation by micturating cystogram. The parents of 20 accepted. Reflux was shown in 3, and in 2 of these there was already renal scarring. The proportion of all infants and young children who have reflux is not accurately known, but the few published surveys of screening of normal infants and young children by micturating cystogram suggest that the prevalence is of the order of 1%. The prevalence in sibs is, then, about 10 times higher. There was a main group of 214 sibs over the age of 4 years. For these the parents were offered investigation by intravenous pyelogram only for those sibs who had a history of recurrent urinary tract infection. If renal scarring was found then a micturating cystogram was done. Of 110 sisters, 12 were `symptomatic', renal scarring was found in 5 of these (1 was on haemodialysis), and reflux was still present in 3. Of 104 brothers 7 were `symptomatic', renal scarring was found in 2 and reflux was present in both. For comparison, the published reports of several surveys of schoolgirls indicate that about 2 in 100 have recurrent urinary tract infection, and in about a quarter of these (0·5%) reflux was present and in about one-eighth (0·25%) renal scarring was present. The prevalence in sibs is, then, 10 to 20 times higher. Similarly in the parents: of 183 mothers 7 (1 was on haemodialysis) and of 181 fathers 2 had renal scarring. The family findings are consistent with multifactorial inheritance, as with other common malformations. Routine investigation, in infancy, of younger sibs of patients with vesicoureteric reflux would identify patients in whom the reflux was recognised very early. These would be valuable for the study of the natural history and management of the disorder, and the degree to which it was possible to prevent the development of renal scarring.